2012
DOI: 10.1371/journal.pone.0037817
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ion Balance and Nitrogen Metabolism in Old and Young Leaves of Alkali-Stressed Rice Plants

Abstract: BackgroundAlkali stress is an important agricultural contaminant and has complex effects on plant metabolism. The aim of this study was to investigate whether the alkali stress has different effects on the growth, ion balance, and nitrogen metabolism in old and young leaves of rice plants, and to compare functions of both organs in alkali tolerance.Methodology/Principal FindingsThe results showed that alkali stress only produced a small effect on the growth of young leaves, whereas strongly damaged old leaves.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 28 publications
(54 reference statements)
1
46
0
1
Order By: Relevance
“…Plant's response to salt not only varies with crop varieties or cultivars but also with the age. For example, in rice older leaves are reported to accumulate higher nitrate content than the younger ones probably because of an upregulated nitrate transporter OsNRT1;2 (Wang et al 2012). Since many cyanobacterial species are endowed with the N 2 -fixing ability, it is relevant to study the effect of high salt on N 2 fixation in general and nitrogenase in particular.…”
Section: Cellular Metabolismmentioning
confidence: 99%
“…Plant's response to salt not only varies with crop varieties or cultivars but also with the age. For example, in rice older leaves are reported to accumulate higher nitrate content than the younger ones probably because of an upregulated nitrate transporter OsNRT1;2 (Wang et al 2012). Since many cyanobacterial species are endowed with the N 2 -fixing ability, it is relevant to study the effect of high salt on N 2 fixation in general and nitrogenase in particular.…”
Section: Cellular Metabolismmentioning
confidence: 99%
“…Countable studies of the basic physiological mechanisms of the alkali stress response were conducted in several plant species including crops and halophytes during recent years. The metal element (K, Ca, Mg, Fe, Cu, Zn) and free ions (NO 3 -, Cl -, H 2 PO 4 -, SO 4 2-) content was decreased in alkali treated plants such as wheat, rice and seabuckthorn, suggesting that high pH stress inhibits the nutrient absorption and disturbs ion balance in plants (Chen et al 2009;Wang et al 2012;Guo et al 2015). Studies have shown that alkali stress also significantly affects photosynthesis and photosynthetic electron transport.…”
mentioning
confidence: 99%
“…Ao contrário da expressão induzida pelo nitrato do NRT1.1, o RNA mensageiro do AtNRT1.2 acumula mesmo na ausência de nitrato, demonstrando ser um componente constitutivo do LATS (Dechorgnat et al, 2011 (Wang et al, 2012a).…”
Section: Introductionunclassified